Gated SPECT Myocardial Perfusion Imaging at status-post Thrombolysis with Streptokinase - Sarker, Azmal K; Naznin, Afroza; Sharmin, Samira; Nasreen, Faria; Nisa, Lutfun; Mandal, Tapati; Begum, Shamim MF; Hussain, Raihan (Bangladesh Journal of Nuclear Medicine, 2022)
Background: Adequate reperfusion by thrombolysis (TL) with streptokinase (STK) after an ST elevation myocardial infarction (STEMI) is associated with better patient outcome. This study described theattributes of patients who at status-post TL underwent gated SPECT myocardial perfusion imaging (GSMPI). Patients and methods: This cross sectional retrospective study was conducted in 2017 on a group of patients who were referred to Nuclear Cardiology Division of National Institute of Nuclear Medicine and Allied Sciences (NINMAS) from February 2005 to October 2016 for GSMPI. Archive was reviewed to include those who received STK with diagnoses of an acute MI, then underwent coronary angiogram (CAG) and then underwent GSMPI. Findings from status-post TL CAG reports were compared with that from GSMPI. Results: Among 1347 patients, 59 (4.4%) were eligible for analysis with mean age of 51.2 ± 9.5 years. GSMPI revealed normal perfusion in 16 (27%), abnormal perfusion in 43 patients with mean LV infarct size at rest of 48.6 ± 17.2% and ischemia in 13 patients with mean ischemic LV of 12.1 ± 9.6%. Mean LVEF in normally perfused LV and in those with perfusion defects were 50.0 ± 18.7% and 39.5 ±14.9%respectively (p = 0.04). CAG was normal in one among 43 patients with abnormal myocardial perfusion. CAG was abnormal in 75% (12 of 16)of patients with normal perfusion. Six (10% of 59) among that 12 with abnormal CAG and normal perfusion had further coronary revascularization (CR). Conclusions: In this series, 27% (16/59) patients who had received STK had normal perfusion and at least in 10% (6/59) the normal perfusion despite an abnormal CAG and without further CR may indicate adequacy of TL using STK. Bangladesh J. Nuclear Med. 23(1&2): 29-36, 2020